Perbandingan Kinerja Sub Sektor Makanan-Minuman dan Farmasi pada Kasus Pertama Covid-19 di Indonesia - Surbakti, Maria Salsalina; Christianti, Ari (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim : This study aims to prove whether the consumer goods sector is a sector that is immune to the Covid-19 pandemic, considering that investment in this sector is an investment in defensive stocks. Design/Methode/Approach : Apply an event study approach, this study will compare the abnormal returns on stocks in the food-beverage and pharmaceutical sub-sector before and after the first case of Covid-19 entered Indonesia. Research Finding : This study showed a significant differences in positive abnormal returns before and after the first case of Covid-19 in the stocks of the food-beverage sub-sector. However, it is different from the pharmaceutical sub-sector. It has a positive abnormal return difference before and after the first case of Covid-19, but it is not significant statistically. Theoretical contribution/Originality : In addition to being influenced by internal factors, stock performance is also influenced by external factors and even external factors outside the market, such as the Covid-19 Pandemic. The Covid-19 Pandemic has impacted a country's economy due to anticipatory policies undertaken to reduce the spread of the virus, including work-from-home and social distancing. Practitionel/Policy implication : Investments in the Consumer Goods sector, in this case, the food-beverage and pharmaceutical sub-sector during the Covid-19 Pandemic, need to be included in the stock portfolio because its performance is stable and tends to increase. Investment in Consumer Goods sector stocks is essential as a defensive stock to stabilize the stock portfolio's performance. Especially during the Covid-19 period, the primary basic human needs are still needed, especially health and the need for PPE (Personal Protective Equipment), vaccines, and medicines the Pandemic. Research limitation : The event window is too short, namely, only five days before the event day and five days after the event. It is recommended that the number of days the event window can be extended so that the abnormal return reaction to the event of the first case of Covid-19 can be better analyzed.